1990
DOI: 10.1111/j.1365-2044.1990.tb14685.x
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous propofol anaesthesia using a computerised infusion system

Abstract: Key wordsAnaesthetics, intravenous; propofol. Equipment; computers, infusion pumps.There has been interest for many years in the maintenance of anaesthesia with intravenous drugs as an alternative to inhalational agents.' The withdrawal of propanidid and Althesin, and the problems related to suppression of adrenocortical function with etomidate, have led to the emergence of propofol as the most suitable intravenous anaesthetic for this purpose. Propofol offers many advantages as a total intravenous anaesthetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
78
0
2

Year Published

1995
1995
2008
2008

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 154 publications
(83 citation statements)
references
References 8 publications
3
78
0
2
Order By: Relevance
“…This finding concurs with other pharmacokinetic evaluations of this algorithm when used for both general anaesthesia [10] and sedation [11], although the bias was more pronounced in our study. However, an advantage of a patient-maintained sedation system is that it allows each patient to titrate the systemic concentration of propofol to a value appropriate for overall comfort.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This finding concurs with other pharmacokinetic evaluations of this algorithm when used for both general anaesthesia [10] and sedation [11], although the bias was more pronounced in our study. However, an advantage of a patient-maintained sedation system is that it allows each patient to titrate the systemic concentration of propofol to a value appropriate for overall comfort.…”
Section: Discussionsupporting
confidence: 93%
“…The TCI system we used is based on an Ohmeda 9000 pump with a modified backbar containing additional computer hardware which is programmed with the pharmacokinetic parameters which describe the distribution and elimination of propofol [10]. Following the additional input of an individual patient's age and weight, a predicted target concentration of propofol (in mg.ml ¹1 ) can be selected and the computer will then make the necessary calculations of the dose of propofol required to achieve and maintain this concentration and infuse the drug accordingly.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of computer-controlled infusions of propofol has been developed to overcome drawbacks of manual schemes of infusion, allowing an easier and more accurate achievement and maintenance of a desired blood concentration of propofol. 4 Coetzee and colleagues 16 have demonstrated that different pharmacokinetic sets may have an impact on the accuracy of target controlled infusion devices, when different pharmacokinetic parameter sets are used. The pharmacokinetic parameter set applied by the Diprifusor is derived from Marsh's modification of the Gepts model, 1~ and provides a median performance error of5.7%, H which can be considered to be acceptable for clinical practice.…”
Section: I~oilmentioning
confidence: 99%
“…Target Controlled Infusion (TCI) systems provide improved convenience and control during TIVA [1]. A TCI system utilizing pharmacokinetics of Propofol is now available in the armed forces hospitals.…”
Section: Methods In Medicine Introductionmentioning
confidence: 99%